2000
DOI: 10.2183/pjab.76.22
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 is absent at the sarcolemma and at perivascular astrocyte endfeet in α1-syntrophin knockout mice

Abstract: Abstract:al-Syntrophin, a member of dystrophin-associated proteins, is expressed at the sarcolemma and at perivascular astrocytes, and participates in protein-protein interactions through its PDZ domain. Aquaporin-4 (AQP4) is the predominant water channel protein in the brain, and also expressed at the sarcolemma of fast-twitch muscle fibers. AQP4 is concentrated in orthogonal array particles (OAPs), and its expression has been reported to be decreased at the sarcolemma of dystrophin-deficient mdx mice. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 3 publications
2
59
0
Order By: Relevance
“…While our work was being completed, independent studies suggested that subcellular localization of AQP4 is altered in ␣-Syn Ϫ/Ϫ skeletal muscle without a change in total expression estimated by immunoblot (24). Although we cannot explain this discrepancy, we have not been able to detect AQP4 in immunoblots of whole membranes from skeletal muscle without prior immunoprecipitation (18).…”
Section: Discussionmentioning
confidence: 81%
“…While our work was being completed, independent studies suggested that subcellular localization of AQP4 is altered in ␣-Syn Ϫ/Ϫ skeletal muscle without a change in total expression estimated by immunoblot (24). Although we cannot explain this discrepancy, we have not been able to detect AQP4 in immunoblots of whole membranes from skeletal muscle without prior immunoprecipitation (18).…”
Section: Discussionmentioning
confidence: 81%
“…51 AQP4 is also associated with Kir 4.1 and with other components of DAPs, 28,48 such as a-syntrophin, which anchored AQP4 in a polarized way on the astrocytic membranes facing the vessels by interaction of its PDZ domain with the C-terminal SSV residues of AQP4. 13,52,53 Furthermore, a-syntrophin-null mice showed AQP4 reduction and redistribution and delayed K þ clearance, 13,31 suggesting that a correct link between AQP4 proteins and DAPs is necessary for an efficient K þ removal.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the organization of AQP4 in distinct pools results from the interaction of AQP4 with different binding partners remains unknown. Studies on dystrophin-deficient animal models mdx mice (Frigeri et al 1998Vajda et al 2004) and asyntrophin null mice (Yokota et al 2000;Neely et al 2001;Bragg et al 2006) suggested an interaction of AQP4 with dystrophin and/or components of the dystrophin-glycoprotein complex (DGC). However, none of the DGC proteins have been shown to directly interact with AQP4.…”
mentioning
confidence: 99%